The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.4049/jimmunol.165.3.1506
|View full text |Cite
|
Sign up to set email alerts
|

A Role for CD40-CD40 Ligand Interactions in the Generation of Type 1 Cytokine Responses in Human Leprosy

Abstract: The interaction of CD40 ligand (CD40L) expressed by activated T cells with CD40 on macrophages has been shown to be a potent stimulus for the production of IL-12, an obligate signal for generation of Th1 cytokine responses. The expression and interaction of CD40 and CD40L were investigated in human infectious disease using leprosy as a model. CD40 and CD40L mRNA and surface protein expression were predominant in skin lesions of resistant tuberculoid patients compared with the highly susceptible lepromatous gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…In our hands sCD40L alone did not stimulate significant release of IL-12. This is in accordance with findings of Yamauchi et al (29), who demonstrated in the mouse model that IL-12 production may be independent of CD40 ligation. Data provided by Han et al (30) show that CD40-CD40L receptor interactions have a lesser role in T-dependent activation of human monocytes, this pair is active if monocytes are primed by IFN␥, that is in accordance with our findigs.…”
Section: Discussionsupporting
confidence: 82%
“…In our hands sCD40L alone did not stimulate significant release of IL-12. This is in accordance with findings of Yamauchi et al (29), who demonstrated in the mouse model that IL-12 production may be independent of CD40 ligation. Data provided by Han et al (30) show that CD40-CD40L receptor interactions have a lesser role in T-dependent activation of human monocytes, this pair is active if monocytes are primed by IFN␥, that is in accordance with our findigs.…”
Section: Discussionsupporting
confidence: 82%
“…The recent implication of CD40/CD40L interactions in the generation of type 1 cytokine responses in human leprosy supports this conclusion. 57 Chemoattraction Ligation of CD40 on ECs, SMCs, M⌽, and T lymphocytes triggers expression and release of chemoattractants overexpressed within human atheroma, such as IL-8, MIP-1␣ (M⌽ inflammatory protein), MIP-1␤, RANTES (regulated on activation, normal T cell expressed and secreted), SDF-1 (stromal cell-derived factor 1), and MCP (monocyte chemotactic protein)-1 ( Table 2 and Figure 2A). 58 -62 These chemokines probably attract and direct T lymphocytes and M⌽ to the atheroma, thus sustaining chronic inflammation.…”
Section: T Helper 1 (Th1) Immune Responsementioning
confidence: 99%
“…A previously described Th1 clone, D103.5 (19,20), derived from a tuberculoid lesion and specific for M. leprae 10-kDa protein, was used as a positive control. This T cell clone produces IFN-␥ in response to IL-12 (data not shown).…”
Section: Emsamentioning
confidence: 99%
“…These data demonstrate that the inability of lepromatous patients to up-regulate IL-12R␤2 correlates with their ineffective Th response to M. leprae. (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) patients were normalized to yield equivalent CD3-␦ mRNA PCR products. PCR with specific primers was then used to detect IL-12R␤1 and IL-12R␤2 mRNA.…”
Section: Il-12r␤2 Expression Correlates With Ag Responsiveness In T Cmentioning
confidence: 99%